A. N. YAKHONTOV IN LATVIA - Veršiņina, Nataļja (Via Latgalica, 2014)
The aim of this article’s research is the recovering of facts about visits of a Pskov poet Alexander Nikolayevich Yakhontov in 1850–1889 to Latvia. Yakhontov’s life was associated with Latvia for forty years, not only in terms of biography, culture and education, but also in the aspect of creativity. However, until now diverse Yakhontov’s connections with Latvia were not systematized and literary studied by local history; archival materials, stored in the Manuscript Department of Pushkin House, and a manuscript of poems by Yakhontov, located in the Pskov museum-reserve, were not introduced in the scientific process. This article releases the first Latvian text in poetry by Yakhontov, who was predisposed to assimilate the cultural environment by the features of his upbringing and education character: translation activities, that began in Tsarskoye Selo Lyceum and entrenched during his European travels in 50–80s, by the interest in culture and life of other people, their history and modernity (books for popular reading “Journey to the Northern Territory of Russia”, “People’s War in 1812” et al.). Being the translator of European literature (J. W. Goethe, F. Schiller, H. Heine, G. E. Lessing, A. Mickiewicz et al.) and the educator in the broadest sense, Yakhontov perceived Latvia as a special area, that combines elements of Russian and European mentalities, aesthetic influence of Slavic and Western cultures. At the same time, the analysis of poetic texts reveals, that he was quite aware of the unique nature of Latvia and the special aesthetics inherent in its discreet seascapes. Yakhontov’s position – as a poet and translator, as well as the specifics of his life circumstances (the need for mud therapy in the resorts of the Baltic states) – was the basis of the scientific methodology, used in the article: biographical, historical and literary, cultural and historical, textual research methods. The study shows, that the main place for Yakhontov’s visits in Courland was Libau (Liepāja – since 1918). Oversea routes of Yakhontov took him through Libau, where he (and later – his wife and son) had the treatment for several times. In the poetic world of Yakhontov Libau held a special place, symbolizing the pristine, wild nature, opposed to the orderly, resort, recreational space. The analysis of previously unpublished epistolary heritage of Yakhontov, compared with the text of the poem “Libau”, helps to clarify its dating, the story of creation and further processing in the book “Poems by Alexander Yakhontov”, edited in 1884. It has been found out that “Libau” opens a lyrical cycle – “On the seaboard”, “By the sea again” and “Calm”, created in 1857 and 1860. It can be concluded, that Yakhontov’s poems inspired by stas in Liepāja and other places of Kurland, can not only identify new, previously unexplored facts of his biography and poetry, but also provide an opportunity to imagine the natural and cultural environment, that characterizes Latvia in this period. Thanks to Yakhontov, the seascape of Libau and experienced moods, which covered an observer in the minutes of contemplation of sea space, can be represented. Being a so-called secondary poet, Yakhontov could convey the uniqueness of experienced sensations, which did not prevent the literary plaque and an abundance of poetic style, which in the context of the Latvian cycle are perceived as the carriers of cultural experience.